Damage tolerance optimization of composite stringer run-out under tensile load. (1st December 2015) - Badalló, P.; Trias, D.; Lindgaard, E.
Abstract: Stringer run-outs are a common solution to achieve the necessary strength, stiffness and geometric requirements of some structural solutions. The mechanical behavior and complexity of such design details requires careful and thorough studies to ensure the structural integrity of the structure. The influence of some geometric variables of the run-out in the interface of the set stringer-panel is crucial to avoid the onset and growth of delamination cracks. In this study, a damage tolerant design of a stringer run-out is achieved by a process of design optimization and surrogate modeling techniques. A parametric finite element model created with python was used to generate a number of different geometrical designs of the stringer run-out. The relevant information of these models was adjusted using Radial Basis Functions (RBF). Finally, the optimization problem was solved using Quasi-Newton method and Genetic Algorithms. In the solution process, the RBF were used to compute the objective function: ratio between the energy release rate and the critical energy release rate according to the Benzeggagh–Kenane mixed mode criterion. Some design guidelines to obtain a damage tolerant stringer-panel interface have been derived from the results.